Two Typical Patterns of Regional PM2.5 Transport for Heavy Air Pollution Over Central China: Rapid Transit Transport and Stationary Accumulation Transport - Wang, Ying; Bai, Yongqing; Zhi, Xiefei; Wu, Kai; Zhao, Tianliang; Zhou, Yue; Xiong, Jie; Zhu, Shoupeng; Zhou, Wen; Hu, Weiyang; Zhang, Ling; Meng, Kai (Frontiers in Environmental Science, 2022)
The regional transport of air pollutants has been identified as a critical factor that affects air quality over downwind receptor areas; however, the regional transport patterns for air pollution episodes remain poorly understood. In this study, we identified two distinct patterns of regional transport: rapid transit transport (RTT) and stationary accumulation transport (SAT), both of which induced severe PM2.5 pollution episodes in central China during 2015–2020. The differences and similarities between the two regional transport patterns of air pollution were characterized by their influencing meteorological factors. Similar meteorological conditions trigger the RTT and SAT, with a high-PM2.5 concentration air mass from the upstream regions transported to the Twain-Hu Basin (THB) by the strong northerly winds with a southward advance of cold air mass. The average rate of increase in the PM2.5 concentration of the RTT (12.5 μg/m3/h) is more than that of the SAT (5.7 μg/m3/h). However, meteorological conditions evolved differently in RTT and SAT. For RTT with the fast passage of cold air, the THB is located behind the strong cold front during the later stage, and these events rapidly ended owing to the northerly winds and wet scavenging of precipitation. For SAT with the slow cold air accumulation, the THB is mainly occupied by a weak high-pressure system with low wind speeds, strong descending airflow, and a low atmospheric boundary layer height, trapping the air pollutants accumulated in the THB and resulting in persistent heavy pollution incidents. This study provides new insights into the meteorological mechanism underlying the formation of severe air pollution episodes over a receptor region owing to the regional transport patterns of air pollutants.